Activating nanomedicines with electromagnetic energy for deep-tissue induction of immunogenic cell death in cancer immunotherapy - Wang, Fengshuo (2023)
Immunotherapy is an attractive approach for cancer therapy, while its antitumor efficacy is still limited, especially for non-immunogenic tumors. Nanomedicines can be utilized to convert the non-immunogenic "cold" tumors to immunogenic "hot" tumors via inducing immunogenic cell death (ICD), thereby promoting the antitumor immune response. Some nanomedicines that can produce local heat and reactive oxygen species upon the stimulation of electromagnetic energy are the main candidates for inducing the ICD effect. However, their applications are often restricted due to the poor tissue penetration depths of electromagnetic energy, such as light. By contrast, ultrasound, X-ray, alternating magnetic field, and microwave show excellent tissue penetration depths and thereby can be used for sonodynamic therapy, radiotherapy, magnetic hyperthermia therapy, and microwave ablation therapy, all of which can effectively induce ICD. Herein, the combination of deep-tissue electromagnetic energy with nanomedicines for inducing ICD and cancer immunotherapy are summarized. In particular, the designs of nanomedicines to amplify ICD effect in the presence of deep-tissue electromagnetic energy and sensitize tumors to various immunotherapies will be discussed. At the end of this review, a brief conclusion and discussion of current challenges and further perspectives in this subfield are provided.